Enterprise Risk Management Practices and Financial Performance of SMEs: Moderating Role of Management Competence in Nigeria (British Journal of Multidisciplinary and Advanced Studies, 2025)
Enterprise risk management (ERM) has become an essential component of modern corporate governance, providing organisations with structured approaches to identifying, assessing, and mitigating risk that may threaten long-term sustainability. This study investigates the moderating effects of management competence on the relationship between ERM and financial performance using a cross-sectional survey design. Primary data was collected through structured questionnaires administered to owners of SMEs. Descriptive and inferential statistics were employed to test the hypothesized relationship. Results reveal a positive and significant relationship between internal environment of ERM and revenue and sales growth of small and medium-scale enterprises (SMEs) in Nigeria, a positive and significant relationship between risk assessment of ERM and revenue and sales growth of small and medium-scale enterprises (SMEs) in Nigeria, a positive and significant relationship between risk response of ERM and revenue and sales growth of small and medium-scale enterprises (SMEs) in Nigeria,  a positive and significant relationship control activities of ERM and revenue and sales growth of small and medium-scale enterprises (SMEs) in Nigeria and a positive and significant relationship between monitoring of ERM and on revenue and sales growth of small and medium-scale enterprises (SMEs) in Nigeria and revenue and sales growth of small and medium-scale enterprises (SMEs) in Nigeria. The study further emphasised that management competence enhances the effectiveness of ERM implementation. The policy implication is that regulators should encourage SMEs to institutionalize ERM practices as a mechanism for achieving financial stability and sustainable growth. Overall, this investigation contributes to the literature by providing empirical evidence from survey-based data that ERM is a driver of superior financial performance.